VIDEO SEQUENCES BACKGROUND REMOVAL ALGORYTHM - R. Kh. Sadykhov; S. A. Kuchuk (Informatika)
An improvement of the method by J.C.S. Jacques, C.R. Jung and S.R. Musse for background removal and video sequences shadow detection is proposed.